PLANNING MORAL EDUCATION PROGRAM (PMEP) BASED ON TOTAL QUALITY MANAGEMENT (TQM) AT SD ISLAM AL-IRSYAD PURWOKERTO - Novan Ardy Wiyani (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2015)
This qualitative research study is intended to determine the steps in Planning Moral Education Program (PMEP) based on Total Quality Management (TQM) at SD Islam Al-Irsyad 02 Purwokerto. Hopefully, the results of this study can be used as a guideline by Islamic elementary school in implementing TQM-based PMEP as preventive measures to address the moral crisis today. The data in this study were collected by using interview techniques and documentation. The data has been collected and analyzed using inductive data analysis techniques. Based on the research results, it was obtained findings that there are four steps involved in planning TQM-based PMEP. First, developing a vision and mission of the school in favor of the PMEP. Second, preparing the quality assurance character and accomplishments with PMEP. Third, developing standards of competence homeroom teachers to support the implementation of PMEP. Fourth, preparing Standard Operating Procedure (SOP) of learners’ morals value to support the implementation of the PMEP.